2019
DOI: 10.3390/ijms20215437
|View full text |Cite
|
Sign up to set email alerts
|

Silenced ZNF154 Is Associated with Longer Survival in Resectable Pancreatic Cancer

Abstract: Pancreatic cancer has become the third leading cause of cancer-related death in the Western world despite advances in therapy of other cancerous lesions. Late diagnosis due to a lack of symptoms during early disease allows metastatic spread of the tumor. Most patients are considered incurable because of metastasized disease. On a cellular level, pancreatic cancer proves to be rather resistant to chemotherapy. Hence, early detection and new therapeutic targets might improve outcomes. The detection of DNA promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“… 2 A recent study also showed the effects of ZNF154 on cell viability and gene expression in vitro. 1 In the present study, ZNF154 upregulation revealed obvious effects on the growth and viability of MGC-803 GC cells, indicating that ZNF154 silencing should be considered as a relevant factor for GC growth. ZNF154 re-expression decreased the mRNA level of HGF, a specifically proliferative gene, in MGC-803 cells, indicating a potential molecular mechanism of ZNF154-mediated inhibition of GC growth.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“… 2 A recent study also showed the effects of ZNF154 on cell viability and gene expression in vitro. 1 In the present study, ZNF154 upregulation revealed obvious effects on the growth and viability of MGC-803 GC cells, indicating that ZNF154 silencing should be considered as a relevant factor for GC growth. ZNF154 re-expression decreased the mRNA level of HGF, a specifically proliferative gene, in MGC-803 cells, indicating a potential molecular mechanism of ZNF154-mediated inhibition of GC growth.…”
Section: Discussionsupporting
confidence: 51%
“…The zinc finger protein 154 ( ZNF154 ) gene have been reported as a tumor suppressor gene in the zinc finger protein family. 1 Compelling evidence has shown that ectopic expression of the ZNF154 gene would suppress tumor cell growth, migration, invasion, and colony formation in nasopharyngeal carcinoma. 2 Studies have shown that the count of methylated CpG sites in the ZNF154 DNA promoter was positively associated with longer survival in respectable pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of gene detection technology, more and more oncogenes and anti-oncogenes have been found to be involved in the occurrence of PC. For example, it was reported that silenced ZNF154 was in relation to longer survival in resectable PC [ 18 ]. Besides, SPOP suppressed PC progression by promoting the degradation of NANOG [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among genes associated with the 38-classifier probes, hypermethylation vs hypomethylation was already reported in different tumor types (with methylation changes being in the same direction as in our study). For instance, hypomethylation of ZNF154 was associated with worsened OS in pancreatic cancer 27 while TTC28 hypomethylation, a target of TP53, was associated with genetic instability and L1-element transpositions in colorectal cancer. 28 Likewise, DCC was reportedly stably hypermethylated in HNSCC, independent of smoking status.…”
Section: Discussionmentioning
confidence: 99%